Bleeding from multifocal heterotopic gastric mucosa in the colon controlled by an H2 antagonist. Issue 6 (June 1988) - Murray, F E; Lombard, M; Dervan, P; Fitzgerald, R J; Crowe, J
Abstract : The sixth documented case of heterotopic gastric mucosa in the large bowel proximal to the rectum is described in a two year old girl with a neural tube defect and recurrent rectal bleeding. Unusual in itself, this case is unique in that the rectal bleeding has been controlled with an H2 receptor antagonist.